Almost perfect sequences with θ=2 - Leung, Ka Hin (2013)
Almost perfect sequences with θ=2 are studied in this paper. Recently Arasu, Ma and Voss [1] studied such sequences and they could only obtain sequences having periods 8, 12 and 28. In this paper, we prove that no other almost perfect sequences exist for the case θ=2.